Are Thoracotomy and/or Intrathoracic Anastomosis Still Predictors of Postoperative Mortality After Esophageal Cancer Surgery?: A Nationwide Study. Issue 5 (November 2017) - Degisors, Sébastien; Pasquer, Arnaud; Renaud, Florence; Béhal, Hélène; Hec, Flora; Gandon, Anne; Vanderbeken, Marguerite; Caranhac, Gilbert; Duhamel, Alain; Piessen, Guillaume; Mariette, Christophe
Abstract : Background: Intrathoracic (vs cervical) anastomosis and a thoracotomy (vs absence) have previously been associated with increasing postoperative mortality (POM). Recent improvements in surgical practices and perioperative management may have changed these dogmas. Objectives: The aim of this study was to evaluate the impact of performing intrathoracic anastomosis and/or thoracotomy on POM after esophageal cancer surgery in recent years. Methods: All consecutive patients who underwent esophageal cancer surgery with reconstruction between 2010 and 2012 in France were included (n = 3286). Patients with a thoracoscopic approach were excluded (n = 4). We compared 30-day POM between patients having received intrathoracic (vs cervical) anastomosis and between those having received a thoracotomy or not. Multivariate analyses and propensity score matching were used to adjust for confounding factors. Results: Patients had either cervical (n = 548) or intrathoracic (n = 2738) anastomosis. Thirty-day POM was higher after cervical anastomosis (8.8% vs 4.9%, P < 0.001). Having received a thoracotomy (n = 3061) was associated with a decreased risk of 30-day POM (5.3% vs 9.3%, P = 0.011). After adjustment for confounding factors, cervical anastomosis was associated with 30-day POM [odds ratio (OR) 1.71; 95% confidence interval (CI) 1.05–2.77); P = 0.032], whereas performing a thoracotomy was not associated with 30-day POM (OR 0.97; 95% CI 0.51–1.84; P = 0.926). Conclusions: Nowadays, intrathoracic anastomosis provides a lower 30-day POM rate compared to cervical anastomosis, and performing a thoracotomy is not associated with POM. Systematic anastomosis neck placement or thoracotomy avoidance is not a relevant argument anymore to decrease POM.